The Assistant Editor Workflow In Film Tuhan Benarkah Kau Mendengarku - Dynia Fitri; Dwi Prio Satrio (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study aims to analyze the workflow of assistant editors in the post-production process of the film Tuhan Benarkah Kau Mendengarku (God, Are You Really Listening to Me?). Assistant editors play a strategic role in managing visual and audio data, maintaining continuity, and providing technical support to the main editor so that the editing process runs efficiently and narratively coherently. This study uses a descriptive qualitative method with a case study approach. Data was collected through direct observation of the editing process, in-depth interviews with the editor and assistant editor, and analysis of documents such as editing logs and project structures. The results of the study show that the assistant editor's workflow has a significant effect on work efficiency, minimization of technical errors, and the smoothness of the editor's creative decision-making. A structured workflow allows editors to focus their energy on building narrative meaning and emotion. This study contributes to film post-production studies by highlighting the often overlooked role of assistant editors, particularly in the context of Indonesian independent film production.